Pakistan Can the United States Secure an Insecure State? - Fair, C. Christine (RAND Corporation, 2010)
The authors exposit likely developments in Pakistan's internal and external security environment over the coming decade; assess Pakistan's national will and capacity to solve its problems, especially those relating to security; describe U.S. interests in Pakistan; and suggest policies for the U.S. government to pursue in order to secure those interests.